Unity and differentiation of legal regulation for the implementation of the right to work in certain categories of employees - Ye. Yu. Podorozhnii (Bulletin of Kharkiv National University of Internal Affairs)
It has been proven that labour relations are a legal relationship between an employer and an employee, which is established on a voluntary basis with regard to the use by the former (i.e., the employer) of the latter’s (i.e., the employee’s) ability to work and is expressed in mutual rights and obligations. It has been noted that in order for legal regulation to be fair, effective and appropriate, it should be based on a number of principles which determine the key priorities and vectors of legal regulation. To a large extent, the principles ensure the unity and integrity of the legal system and the legal regulation mechanism.